Augmented Reality, Surgical Navigation, and 3D Printing for Transcanal Endoscopic Approach to the Petrous Apex. Issue 4 (October 2018) - Barber, Samuel R.; Wong, Kevin; Kanumuri, Vivek; Kiringoda, Ruwan; Kempfle, Judith; Remenschneider, Aaron K.; Kozin, Elliott D.; Lee, Daniel J.
Otolaryngologists increasingly use patient-specific 3-dimensional (3D)–printed anatomic physical models for preoperative planning. However, few reports describe concomitant use with virtual models. Herein, we aim to (1) use a 3D-printed patient-specific physical model with lateral skull base navigation for preoperative planning, (2) review anatomy virtually via augmented reality (AR), and (3) compare physical and virtual models to intraoperative findings in a challenging case of a symptomatic petrous apex cyst. Computed tomography (CT) imaging was manually segmented to generate 3D models. AR facilitated virtual surgical planning. Navigation was then coupled to 3D-printed anatomy to simulate surgery using an endoscopic approach. Intraoperative findings were comparable to simulation. Virtual and physical models adequately addressed details of endoscopic surgery, including avoidance of critical structures. Complex lateral skull base cases may be optimized by surgical planning via 3D-printed simulation with navigation. Future studies will address whether simulation can improve patient outcomes.